Aspisol inhibits tumor growth and induces apoptosis in breast cancer - Zhu, X.G.; Tao, L.; Mei, Z.R.; Wu, H.P.; Jiang, Z.W. (Experimental Oncology, 2008)
Nonsteroidal anti-inflammatory drugs inhibit cell proliferation and induce apoptosis in various cancer cell lines, which is considered to be an important mechanism for their anti-tumor activity and cancer prevention. However, the molecular mechanisms through which these compounds induce apoptosis are not well understood. Aim: to determine the effects of nonselective cyclooxygenase-2 (COX-2) inhibitor, aspisol on breast cancer cells in vitro and in vivo. Methods: The cytotoxic activity of aspisol was evaluated by MTT assay. The apoptosis index of cells was measured by flow cytometry. Immunohistochemical staining was used to detect expressions of COX-2 and caspase-3 in MDA-MB-231 cells. The expression of bcl-2 and bax was analyzed by Western blot analysis. The content of prostaglandin E2 (PGE2) in MDA-MB-231 cells was estimated by ELISA. In vivo apoptosis of the tumor cells was detected by the terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL). Results: Our results showed that aspisol reduced viability of MDA-MB-231 cells in time- and dose- dependent fashions and induced apoptosis by increase of caspase-3 and bax expressions while decrease of COX-2 and bcl-2 expression in vitro. In addition, exposure to aspisol decreased the basal release of PGE2. In vivo, aspisol also inhibited the proliferation of breast cancer cells and induced their apoptosis. Conclusions: Our in vitro and in vivo data indicated that the antitumor effects of aspisol on breast cancer cells was probably mediated by the induction of apoptosis, and it could be linked to the downregulation of the COX-2 or bcl-2 expression and up-regulation of caspase-3 or bax expression.